2010
DOI: 10.3174/ajnr.a2112
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatic Encephalopathy: Diffusion-Weighted and Fluid-Attenuated Inversion Recovery Findings, and Correlation with Plasma Ammonia Level and Clinical Outcome

Abstract: BACKGROUND AND PURPOSE:In acute hepatic encephalopathy, MR imaging abnormalities have been described in the PVWM, thalami, and corticospinal tracts. We sought to determine characteristic regions of involvement on FLAIR and DWI, to evaluate their reversibility, and to correlate MR imaging extent with clinical severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…In the September 2010 issue of AJNR, we used a similar term of "acute hepatic encephalopathy" (most of the patients had hyperammonemia), and the terms could perhaps be considered interchangeable (notably, both would result in the acronym AHE). 2 We thank them for describing their findings, which are similar to the cases we described that, in our opinion, lie at the severe end of the spectrum of AHE. Of particular note is that 2 of their 4 patients died.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In the September 2010 issue of AJNR, we used a similar term of "acute hepatic encephalopathy" (most of the patients had hyperammonemia), and the terms could perhaps be considered interchangeable (notably, both would result in the acronym AHE). 2 We thank them for describing their findings, which are similar to the cases we described that, in our opinion, lie at the severe end of the spectrum of AHE. Of particular note is that 2 of their 4 patients died.…”
supporting
confidence: 56%
“…Indeed, our study did not find a significant correlation between plasma ammonia levels and the initial clinical severity of AHE, though we found that the initial clinical severity, the plasma ammonia level, and the extent of FLAIR and DWI abnormalities on MR imaging all significantly correlated with patient outcome. 2 Thus, while ammonia is inextricably linked to the pathogenesis of AHE, it may be a bit misleading to use the term "hyperammonemic encephalopathy," because ammonia is but 1 (albeit quite important) precursor to the development of encephalopathy. Both our study and that of U-King-Im et al 1 would suggest that prospective monitoring of serum ammonia levels and MR imaging findings, along with other clinical and laboratory tests, could further delineate the pathogenesis of this potentially reversible disorder.…”
mentioning
confidence: 99%
“…Plasma ammonia levels have been shown to correspond to the extent of MRI abnormality. 4,9 It is unclear why the insular and cingulate cortices are particularly susceptible to toxic effects of ammonia. Ammonia crosses the blood-brain barrier through passive diffusion and cation channels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study by McKinney et al (8) , five anatomical areas were identified-posterior limb of internal capsule, thalamus, insular cortex, periventricular white matter and diffuse cortical involvement. Each of these sites were evaluated for all patients and the extent of involvement on magnetic resonance imaging and correlated with initial clinical severity.…”
Section: Discussionmentioning
confidence: 99%